Degradation of microcystin-lr using sulfate radicals generated through photolysis, thermolysis and e- transfer mechanisms - De La Cruz, Armah A.; Dionysiou, Dionysios Demetriou D.; Antoniou, Maria G. (My University, 2010)
This study explores the potential use of sulfate radical-based advanced oxidation technologies (SR-AOTs) for the degradation of the naturally occurring hepatotoxin, microcystin-LR (MC-LR). The generation of sulfate radicals was achieved by activation of the oxidants persulfate (PS) and peroxymonosulfate (PMS) through electrophilic transition metal cations (Ag+ and Co2+, respectively), radiation (UV 300 < λ < 400 nm) and/or heat (T = 30 °C). These systems were compared to more frequently used AOTs systems in industrial applications; the Fenton Reagent (FR) and hydrogen peroxide coupled with heat and radiation. Even though SO4{radical dot}- has similar redox potential to hydroxyl radical (HO{radical dot}), to the best of our knowledge, SR-AOTs have not been tested for the degradation of cyanotoxins. In this study, PMS was activated very efficiently with Co2+ at neutral pH and increasing catalyst concentration resulted in dramatic increase of the initial rates of degradation that reached a plateau for CCo(II) ≥ 1 mg. Based on the optimum pH conditions for each system, the efficiency order is Co2+/PMS > Fe2+/H2O2 ≫ Ag+/PS, which we believe is associated with the energy of the lower unoccupied molecular orbital of the oxidants. When UV (300 < λ < 400 nm) radiation was used, the PS system was more efficient than PMS and H2O2 at all different oxidant concentrations. Since, the UV lamps used in the study emit light at a range of wavelengths (300 < λ < 400 nm), the activation of the oxidants is believed to be caused by the emission spectra and not just λmax = 365 nm. At acidic conditions, the PS/UV (300 < λ < 400 nm)/pH 3 and PMS/UV/pH 3 systems were most efficient and required the least amount of energy to reduce the toxin concentration by one order of magnitude. When thermal activation was used, PMS yielded the highest degradation efficiency (∼77%) compared to 52% for the PS and less then 2.5% for H2O2.
Keywords: Cyanotoxins; e- transfer mechanisms; Fenton Reagent; Hydrogen peroxide; Microcystin-LR; Oxidants; Peroxymonosulfate; Persulfate; Photolysis; Sulfate radicals; Thermolysis